2020
DOI: 10.3390/pathogens9100782
|View full text |Cite
|
Sign up to set email alerts
|

Low Pathogenic Strain of Infectious Pancreatic Necrosis Virus (IPNV) Associated with Recent Outbreaks in Iranian Trout Farms

Abstract: Infectious pancreatic necrosis (IPN), first described as acute viral catarrhal enteritis, is a highly contagious disease with variable pathogenicity that has been linked to genetic variation in the viral VP2 gene encoding the capsid protein. In this study, the IPN virus (IPNV) is isolated from the moribund fish from five of fourteen Iranian trout farms from 2015 to 2017. The affected fish showed mortality rates ranging from 20% to 60%, with the main clinical signs of exophthalmia, darkened skin, and mild abdom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…IPNV has a wide host range, such as rainbow trout [ 44 ] and Atlantic salmon [ 8 ]. It can also infect eels ( Anguilla anguilla ) [ 41 ] Atlantic cod ( Gadus morhua ) [ 45 ], Greenland halibut ( Sebastes mentella ) [ 45 ], deepwater redfish (S alvelinus alpinus ) [ 45 ], Arctic char ( Scophthalmus maximus ) [ 45 ] and pike ( Esox lucius L.) [ 46 ]. Because triploid rainbow trout is the main aquaculture species maintained in China, most of the fish samples tested in this study were from rainbow trout, and this species was the main host of the Chinese IPNV isolates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IPNV has a wide host range, such as rainbow trout [ 44 ] and Atlantic salmon [ 8 ]. It can also infect eels ( Anguilla anguilla ) [ 41 ] Atlantic cod ( Gadus morhua ) [ 45 ], Greenland halibut ( Sebastes mentella ) [ 45 ], deepwater redfish (S alvelinus alpinus ) [ 45 ], Arctic char ( Scophthalmus maximus ) [ 45 ] and pike ( Esox lucius L.) [ 46 ]. Because triploid rainbow trout is the main aquaculture species maintained in China, most of the fish samples tested in this study were from rainbow trout, and this species was the main host of the Chinese IPNV isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Both two types of IPNV can cause mass death in trout juveniles. A previous study showed that genogroup V IPNV strains have a greater negative effect on rainbow trout compared with genogroup I IPNV strains [ 46 ]. However, Tapia, Barría [ 47 ] showed that genogroup I IPNV strains caused higher mortality in rainbow trout when they conducted artificial challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Genogroup 6 (A4) was also detected from rainbow trout farms in Iran (Soltani et al, 2015). Turkey and Iran are exporting rainbow trout eggs from many countries such as the United States of America, the United Kingdom, the Republic of South Africa, Azerbaijan and apart from the European continent, which A2 (Sp) are widely found (Ahmadivand et al, 2020; Cutrin et al, 2004; Romero‐Brey et al, 2009). And it is crucial that A3 (Ab) and A4 (He) serotypes, previously reported in Iran, Europe and America, have not been reported in Turkey yet (Cutrin et al, 2004, Soltani et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…All the isolates evaluated in this study have been shown to have PTA and PTE virulence motifs. Recent outbreaks in rainbow trout, caused by PTA and PTE motifs of IPNV, known previously nonvirulent for Atlantic salmons, are moderate virulent for rainbow trouts (Ahmadivand et al, 2020; Panzarin et al, 2018; Tamer et al, 2021). When the epidemiological data and sequence results are compared, it is thought that both virulence motifs (PTA and PTE) can be pathogenic for rainbow trout.…”
Section: Discussionmentioning
confidence: 99%
“…The PCR was performed using the following temperature profile: denaturation at 10 min 95 • C followed by 35 cycles of 94 • C for 30 s, 52 • C (IHNV) or 58 • C (VHSV) for 35 s and 72 • C for 45 s, and a final extension at 72 • C for 10 min. Samples were additionally screened for IPNV using PCR assays by previously published primers with an amplicon of 405 bp region of the VP2 gene, according to Ahmadivand et al [23]. The amplification products were resolved with electrophoresis using a 1.5% agarose gel and visualized under UV light.…”
Section: Rt-pcr Assaymentioning
confidence: 99%